Rosmarinus officinalis and Centella asiatica Affect Interleukin-6 Zebrafish Larvae Induced High Glucose - Prastiwi, Fajar Dwi; Lamadi, Sutini; Khotimah, Husnul; Wiyasa, I Wayan Arsana; Raras, Tri Yudani M. (Medical Laboratory Technology Journal, 2024)
Gestational Diabetes Mellitus (GDM) is diabetes that occurs during pregnancy. GDM is characterized by hyperglycemia. Hyperglycemia causes an inflammatory response characterized by the excretion of pro-inflammatory cytokines, one of which is IL-6. Centella asiatica and Rosmarinus officinalis are known as anti-diabetic and anti-inflammatory. This study aims to study the effect of the combination of nanoemulsion Centella asiatica and Rosmarinus officinalis on the expression of Interleukin-6 in Zebrafish larvae induced by 3% glucose. Hyperglycemia is known from increased levels of Phosphoenolpyruvate carboxykinase in Zebrafish larvae. Phosphoenolpyruvate carboxykinase and Interleukin-6 expression were measured by conventional PCR method. The combination of Rosmarinus officinalis nanoemulsion and Centella asiatica was given with three different doses, namely at a concentration of 2.5, 5 and 10 µg/mL. The statistical analysis used was One Way ANOVA to measure Interleukin-6 expression levels. The results of this study prove that the combination of Rosmarinus officinalis and Centella asiatica nanoemulsions reduces the expression of Interleukin-6. The dose closest to the negative control was at a concentration of 5 μg/mL, although the final result was statistically significant (p<0.05). In conclusion, combining nanoemulsion Centella asiatica and Rosmarinus officinalis with the right dose reduced levels of Interleukin 6 in zebrafish larvae induced by high glucose.